Factors influencing entrepreneurial intention: the moderating role of entrepreneurship education - Siti Farhah Fazira Shamsudin (2018)
Entrepreneurship is viewed as one of the key economic growth strategies to advance a country’s economic development and to maintain its competitiveness in coping with the growing trends of globalisation. However, despite the initiatives and efforts reserved by the government and higher education institutions to teach entrepreneurship, the choice to participate in business after graduation is still low among graduates. Therefore, this study aimed to explore the factors affecting students’ intentions to be an entrepreneur. Furthermore, it also aimed to examine the moderating effects of entrepreneurship education in enhancing entrepreneurial intentions among Malaysian university students. A total of 375 final year Business students from eight public universities in Malaysia participated in this study. Data were collected through personal-administered survey questionnaires. The Partial Least Squares approach to Structural Equation Modelling (PLS-SEM) was the main statistical technique employed in this study. Findings of this study noted significant positive effects on the relationship between innovativeness, risk- taking propensity, family background and supportive environment with students’ entrepreneurial intentions. Findings also discovered a negative and significant effect of the relationship between entrepreneurship barrier and students’ intentions to be an entrepreneur. Moreover, in terms of moderating effects of entrepreneurship education, this study found a significant support on the moderation of entrepreneurship programme on the relationship between supportive environment and entrepreneurial intention. In addition, findings of this study also found out that service quality of entrepreneurship education moderates the relationship between entrepreneurship barrier and intention. Several plausible reasons were discussed. Based on the findings, this study proved to provide the theoretical implication as it managed to present empirical evidence on factors that influence entrepreneurial intention. The limitation and direction for further research were also discussed.